2013
DOI: 10.3892/ijo.2013.2118
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative treatment of locally advanced esophageal carcinoma

Abstract: Esophageal cancer (EC) is an aggressive malignancy with increasing incidence worldwide. Surgery is still the most effective treatment, however, both the high rate of local and distant recurrences and surgery-related complications led us to investigate new preoperative strategies. In this review, we discuss the role of neoadjuvant therapy for locally advanced EC with a focus on preoperative chemoradiation (trimodality treatment). Furthermore, the last fifteen years of published literature and our experience hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Current treatment generally employs surgical resection combined with chemotherapy and radiotherapy for advanced ESCC. However, both the high recurrence rate and strong systemic toxicity of the anticancer treatments led us to investigate new agents to improve the therapeutic effect (2).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment generally employs surgical resection combined with chemotherapy and radiotherapy for advanced ESCC. However, both the high recurrence rate and strong systemic toxicity of the anticancer treatments led us to investigate new agents to improve the therapeutic effect (2).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The metaanalysis conducted by Arnott et al reported a poor benefit rate with preoperative radiotherapy alone. 15 Burmeister BH et al found that most published randomized clinical trials comparing local modalities have not shown a survival benefit but rather one in terms of local control and improved resectability where surgery has been involved. 16 Upfront surgery with adjuvant therapy and survival, in present present study 4 patients who received postoperative radiation therapy 2 patients expired following surgery due to pulmonary sepsis, it was observed that survival was not improved significantly with the addition of RT, comparing with the study done by Xion et al included 495 patients with SCC of the oesophagus who received postoperative radiation therapy (n=220) or surgery alone (n=275) and survival was not improved significantly with the addition of RT (only change observed was of from 32% to 41%).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that surgery was the best and only primary treatment for most GCs that had spread to lymphomas. Adjuvant therapies such as CT and chemoradiotherapy can reduce the complications of the disease that has spread to lymphomas (9). In a review study conducted by Repka et al In the United States, various evidences were examined to evaluate the effect of RT on the treatment of GC.…”
Section: Figurementioning
confidence: 99%
“…Some usual CT medicines are 5-Fluorouracil, Cisplatin, Capecitabine, Fluropyrimidine, and Oxaliplatin. For HER2+ patients in stage four, the trastuzumab is used, but in CT, before surgery, 5-Fluorouracil, Cisplatin, and Capecitabine are common (9). Although all of these treatments are acceptable according to the recommended protocols, their outcomes have not been fully studied especially in eastern countries.…”
Section: Introductionmentioning
confidence: 99%